A HYBRID MICRO GENERATION SYSTEM FOR A SMALL SCALE BUILDING IN URBAN AREA - Attaianese, Erminia; Duca, Gabriella; Caturano, Umberto; Coppola, Nunzia; Scapicchio, Sara (European Scientific Journal, ESJ, 2014)
The rising energy demand and the increased saving needs in building sector pushed in the last years the development of hybrid systems combining different energy sources, which can optimize available renewable resources, exceeding limitation deriving from each source. Research and market pay particular attention on questions resulting from integration of different systems and technical solutions, with the aim of maximizing their viability in terms of yielded energy and compatibility with planning and environmental regulations in any specific installation site. Funded by Italian Ministry of Environment (MATTM) and developed by Department of Architecture of University of Naples Federico II in partnership with two private companies, the research project TeCNaRE experimented a hybrid micro-generation system that exploits soil thermal inertia and wind energy, merging two renewable sources generally not combined. The hybrid renewable microgeneration system investigated in this study is a ground source heat pump which is co-powered by energy provided by a ground mounted micro-wind turbine, to meet the heating and cooling demand of a small building in urban area. Research brought to a prototypal installation on a demonstration building located on Posillipo hill, a valuable area of the city of Naples (Southern Italy), where landscape is strictly preserved and protected.